Breeding improvement of amaranth (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The article highlights modern approaches to the breeding improvement of amaranth (Amaranthus spp.) as a promising niche crop capable of ensuring food and functional security under global climate change conditions. It provides an analysis of morphological, biochemical, and genetic traits of breeding value, including protein, lysine, and squalene content, as well as indicators of yield, adaptability, and resistance to abiotic stresses. The prospects for using biotechnological methods, such as marker-assisted selection, genome editing (CRISPR/Cas9), and the integration of foreign germplasm to enhance adaptability and nutritional value of new varieties, are discussed. The results of field studies and a comparative assessment of varieties based on agronomic indicators are presented. Emphasis is placed on the need for further development of genetic resources, molecular breeding, and agronomic support for amaranth cultivation in various agro-climatic zones of Ukraine. Strategies are proposed for combining traditional and modern breeding methods to develop high-yielding, stress-resistant, and nutritionally valuable amaranth varieties capable of effectively responding to the challenges of modern agriculture.
Keywords: amaranth; breeding; productivity; abiotic stresses; genetic resources; varietal diversity; biotechnology; adaptability